2019
DOI: 10.3390/s20010231
|View full text |Cite
|
Sign up to set email alerts
|

Hourly PWV Dataset Derived from GNSS Observations in China

Abstract: The rapid variation of atmospheric water vapor is important for a regional hydrologic cycle and climate change. However, it is rarely investigated in China, due to the lack of a precipitable water vapor (PWV) dataset with high temporal resolution. Therefore, this study focuses on the generation of an hourly PWV dataset using Global Navigation Satellite System (GNSS) observations derived from the Crustal Movement Observation Network of China. The zenith total delay parameters estimated by GAMIT/GLOBK software a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Similar investigations were later carried out over China and East Africa for ERA5 by Zhao et al. (2020) and Ssenyunzi et al. (2020), respectively.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Similar investigations were later carried out over China and East Africa for ERA5 by Zhao et al. (2020) and Ssenyunzi et al. (2020), respectively.…”
Section: Introductionsupporting
confidence: 65%
“…Therefore, it is essential to unify the PWV values at different heights to reduce the impact of these height differences. Previous studies (Leckner et al., 1978; Li et al., 2020; Wang et al., 2020; H. Zhang et al., 2019; Zhao et al., 2020) have used the widely common empirical correction function of PWV (E‐PWVC model) to unify the PWV values of stations at different heights. However, due to the significant seasonal variations in PWV over the TP (Zhang et al., 2013), systematic errors are generated when using such a simple correction formula to adjust the PWV.…”
Section: Development Of Two Enhanced Models Over the Tpmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested our model with radiosonde data from 2011 to 2019, and the results showed that our model has the best accuracy. The spatial distribution characteristics of the PWV are consistent with other studies in different years [39,40]. There are bimodal characteristics of the PWV in Southern China, and the formation mechanism of the bimodal characteristics remains to be further studied.…”
Section: Discussionsupporting
confidence: 88%
“…PWV is greatly affected in the vertical direction, and the PWVs at different heights must be unified to reduce the impact of height differences on the PWV comparisons. The empirical correction model of PWV is used as follows (Zhang et al, 2019a;Zhao et al, 2019b):…”
Section: Comparison Of Gnss-derived Pwv With Radiosonde-derived Pwvmentioning
confidence: 99%